Effectiveness of peer tutoring program on students' academic performance for engineering course / Fei Ha Chiew ... [et al.] - Fei, Ha Chiew; Petrus, Clotilda; Othman, Siti Zaidah; Nyuin, Joe Davylyn; Ung, Hua Lau (Universiti Teknologi MARA Cawangan Sarawak, 2021)
This study investigated the effectiveness of a peer tutoring program that was implemented for Basic Solid Mechanics course, as an intervention program to improve students' performance in the course. Ten tutors were chosen to provide tutoring services to an experimental group of 36 tutees. Tutees were required to answer an entry test before the intervention program, and another exit test after the program. A control group which shared the same instructor in their lecture classes was included in the study. Comparison between the performances for entry and exit tests of both experimental and control groups were made. Analyses showed an increase in the percentage of students that passed the exit test from the experimental group. The average marks for the experimental group in the exit test also increased, compared to their marks in the entry test. A Mann- Whitney U test conducted indicated a significant difference between the gain scores of the experimental group and control group. A further metaanalysis revealed a large effect size, signaling the practical significance of the results. The findings demonstrated the effectiveness of the peer tutoring intervention program on students' performance of the course.